Mechanical performance and properties of concrete with recycled concrete aggregates from demolition wastes in the Philippines - Togores, Nikko L.
With the current growth of economy in the Philippines, it will accompany a growth in demand for construction matelials and an increase in construction and demolition wastes. Alternatives for this materials will be in need and most of them may come from recycled materials. Among the wastes clrrrently being dumped in landfills are demolished concrete that could be turned into recycled concrete aggregate (RCA) that could be used as a replacement to natural aggregates (NA) in concrete production in. This research studied the mechanical properties of RCA and its effect on the strength of concrete, and detennined the optimum RCA:NA replacement ratio that would satisfy tile design strength and would be practical in construction. In this research it was observed that there is a decrease in specific gravity (SG) (ave. of 14% for Dry Bulk SG and 12% for Wet Bulk SG) and a large increase in absorption (ave. of 65%) in RCA compared to NA. There is also a decrease in slump or workability of concrete as the RCA: NA replacement ratio increases. Also, at 28 days of curing it was determined that recycled aggregate concrete (RCA) having a 70% RCA:NA replacement ratio can have strengths that are statistically the same as natural aggregate concrete (NAC). However, the strength of the 70% RCA:NA replacement ratio RCA might be dne to the decrease of the effective water-to-cement (W/C) ratio due to the high absorption of the RCA, thus increasing the water requirement of the concrete mix. Thus using 30% RCA:NA replacement ratio may be more optimal for construction.